2012
DOI: 10.1158/0008-5472.can-11-3722
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Mutanome for Tumor Vaccination

Abstract: Multiple genetic events and subsequent clonal evolution drive carcinogenesis, making disease elimination with single-targeted drugs difficult. The multiplicity of gene mutations derived from clonal heterogeneity therefore represents an ideal setting for multiepitope tumor vaccination. Here, we used next generation sequencing exome resequencing to identify 962 nonsynonymous somatic point mutations in B16F10 murine melanoma cells, with 563 of those mutations in expressed genes. Potential driver mutations occurre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
616
2
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(668 citation statements)
references
References 52 publications
22
616
2
11
Order By: Relevance
“…Note that only combinations of adjacent missense mutations supported on the same read of WES data were considered and only neoantigens predicted in four of four biological replicates were included in our analysis. This neoantigen list was combined with a previously published list of neoantigens 24, 36 . Briefly, a list of nanoparticle bound proteins obtained from the mass spec data was run through a python script to find proteins with at least one predicted neoantigen or previously identified neoantigen.…”
Section: Methodsmentioning
confidence: 99%
“…Note that only combinations of adjacent missense mutations supported on the same read of WES data were considered and only neoantigens predicted in four of four biological replicates were included in our analysis. This neoantigen list was combined with a previously published list of neoantigens 24, 36 . Briefly, a list of nanoparticle bound proteins obtained from the mass spec data was run through a python script to find proteins with at least one predicted neoantigen or previously identified neoantigen.…”
Section: Methodsmentioning
confidence: 99%
“…2). Compared with current published studies, our TRP-2-based therapeutic nanoparticle vaccine is very potent at the low doses used for antigen and adjuvant (18,39,40). Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 89%
“…Most of the latest and more advanced clinical trials for TSA-specific vaccines are based on the administration of Ag cocktails 47,66 . Another recent approach delivers multiple Ags as an individualized neo-antigen mRNA-polytope vaccine 67-69 which represents a promising alternative to administration of antigens via synthetic peptides. Eliciting a broad immune response against several tumor-specific CD4 and CD8 epitopes has major advantages.…”
Section: Discussionmentioning
confidence: 99%